Survey on oral health status of second-grade primary school students in Suzhou City - ZHANG Yuwen, LI Bei, GE Bing, ZHU Ye, WANG Xiaozhen, BAI Lu, ZHU Peng (Kouqiang yixue)
Objective To investigate the oral health status of second-grade primary school students in Suzhou, provide baseline data for evaluating Suzhou’s “Bright Eyes and Healthy Teeth” public health project, and offer reference for formulating oral health policies for students in Suzhou. Methods A multi-stage, stratified, random sampling method was used to select 1 640 second-grade primary school students from 10 districts(county-level cities) across Suzhou. The oral health survey of primary school students in Suzhou was designedbased on WHO “Basic Methods for Oral Health Surveys”(5th edition). A survey on the students’ oral health status was conducted. Results The caries prevalence, mean DMFT(Decayed, Missing, Filled Teeth), and caries filling rate for primary teeth among second-grade students in Suzhou were 80.73%, 4.25, and 24.48%, respectively. For permanent teeth, the caries prevalence, mean DMFT(Decayed, Missing, Filled Teeth), and caries filling rate were 30.30%, 0.62, and 16.96%, respectively. Specifically, the caries prevalence, mean DMFT, and filling rate for the first permanent molar were 29.88%, 0.59, and 16.94%, respectively. The pit and fissure sealing rate for the first permanent molar was 13.74%. Additionally, the detection rate for gingival bleeding was 58.05%, and for dental calculus, 49.15%. Conclusion The oral health status of second-grade primary school students in Suzhou is concerning.The caries prevalence rate for both primary and permanent teeth is high, while the filling rate is relatively low. Prior to the implementation of oral health programs, the pit and fissure sealing rate for the first permanent molars was low, with significant differences observed between urban and rural areas, as well as among different districts(or county-level cities).